2021
DOI: 10.7717/peerj.12329
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the spike and nucleocapsid protein of porcine epidemic diarrhea virus strain in Vietnam—a molecular potential for the vaccine development?

Abstract: Background Porcine epidemic diarrhea virus (PEDV) is a dangerous virus causing large piglet losses. PEDV spread rapidly between pig farms and caused the death of up to 90% of infected piglets. Current vaccines are only partially effective in providing immunity to suckling due to the rapid dissemination and ongoing evolution of PEDV. Methods In this study, the complete genome of a PEDV strain in Vietnam 2018 (IBT/VN/2018 strain) has been seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Studies have reported that the amino acid variations of the PEDV S protein might result in antigenicity differences [15,33]. As a consequence, the selection of conserved antigen regions is very important for total antibody level and neutralizing antibody detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that the amino acid variations of the PEDV S protein might result in antigenicity differences [15,33]. As a consequence, the selection of conserved antigen regions is very important for total antibody level and neutralizing antibody detection.…”
Section: Discussionmentioning
confidence: 99%
“…These structural proteins have already been used as target coating proteins to establish iELISAs for detecting anti-PEDV antibodies [11]; however, researchers found that N protein or M protein-based iELISAs exhibit high cross-reactivity for other swine coronaviruses [12,13] while S proteinbased iELISA is more sensitive than N protein one [11]. Meanwhile, it has been proven that the S protein has higher antigenicity than other ones, and anti-S antibodies produced in PEDV-infected pigs could persist longer than anti-N antibodies [14,15]. Moreover, because the S protein harbors more virus-neutralizing epitopes, it is also recognized as the target for neutralizing antibody induction [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of PEDV has been complex and rapid, with potential recombination events occurring between the G1a and G2 lineages and leading to new lineages such as S-INDEL (G1b) and the newly identified G2c [ 10 , 27 , 28 , 29 ]. Changes in the S gene through mutation and recombination can alter the pathogenicity of the virus and its ability to infect different tissues or species [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The S protein is also vital for infection, as it induces the production of neutralizing antibodies and is a key target for vaccine development, both for live attenuated and subunit vaccines [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite vaccination, severe outbreaks of PED have been occurring continually in pig herds throughout the whole country. The reasons for vaccine failure might be found by examining genetic variations within the genomes of the currently circulating PEDV strains [ 28 , 29 , 31 , 32 ]. There remains a need for molecular analysis of the S1 protein sequences of the clinical strains recently or currently circulating in Vietnam.…”
mentioning
confidence: 99%
“…The complete S1 spike sequence phylogeny will give higher resolution, and the complete genomic sequence analysis will better resolve the taxonomic status of these isolates. Further detailed genome characterization and protein structure prediction, as well as testing their antigenicity/immunogenicity will be useful for developing a strategy for making alternative vaccines in the near future [ 32 ]. This research highlights the need for frequent vaccine updates to ensure protection efficacy despite the continuous evolution of PEDV [ 37 , 41 , 42 ].…”
mentioning
confidence: 99%